Instability, Conflict and Political Violence in Chile, 1925-1941 [Instabilité, Conflits Et Violence Politique Au Chili, 1925-1941] [Instabilidade, Conflito E Violência Política No Chile, 1925-1941] [Inestabilidad, Conflictividad y Violencia Política en Chile, 1925-1941] - Goicovic-Donoso, I (Sello editorial Universidad del Atlantico, 2021)
In the early 1920s, Chile experienced institutional instability due to the oligarchic regime crisis and the political consolidation of class movements. This crisis, which extended right until the arrival to power of the Frente Popular (1938), escalated to increasing levels of violence, involving both antagonist groups and ideologically related movements. This article analyses the circumstances and actors that shaped the scenarios of political conflict in Chile and identifies the dynamics that violence acquired. © 2021 Sello editorial Universidad del Atlantico. All rights reserved.